Implementation Of Army Leadership In Increasing The Behavior Of Defending The State - Manurung, Bill Clinton; Risdhianto, Agung; Surjaatmadja, Surrachman (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Defending the country now is not only about fighting with weapons, but also with skills, skills and expertise in their respective fields for the advancement of the Indonesian nation. The TNI AD as part of the TNI, the main component of the Indonesian National Army in the field, together with other elements of the Indonesian National Armed Forces, must be able to strengthen and use existing resources to be ready to be mobilized. This article was compiled based on a literature study using a descriptive qualitative approach. Leadership is the ability to influence subordinates or a group of people to work together to achieve organizational goals. The military leadership is to successfully handle defense tasks, where social and political stability factors are most important. Development of state defense cadres can become a regular program that can be held throughout Rindam Indonesia.